Two New Cases and Literature Review of CLIPPERS Syndrome with Long-Term Follow-up - Kamişli, Özden (Noro Psikiyatr Ars, 2017)
Chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids (CLIPPERS) is an inflammatory disorder of the central nervous system. The pathophysiology of CLIPPERS is unknown. The disease has characteristic radiological lesions located in the pons, bulbus, and cerebellum. Here we report two new cases and review the literature on CLIPPERS syndrome. A 35-year-old woman presented with a 2-month history of progressive double vision, vertigo, gait ataxia, nausea, and vomiting. The second case was that of a 40-year-old Iraqi man who presented with a 3-month history of vertigo, headache, and gait ataxia. Diagnosis of CLIPPERS was established based on findings of punctate, nodular enhancing lesions in the pons and bulbus in the first case and in the cerebellum in the second. Our patients responded well to steroid therapy and remained relapse-free for 2 years. CLIPPERS is a rare autoimmune disorder with characteristic radiological findings. Long-term immunosuppressive therapy is necessary for treatment.